Development initiatives, micro-enterprise performance and sustainability - Wan Nurulasiah Wan Mustapa; Abdullah Al- Mamun; Mohamed Dahlan Ibrahim (2018)
Towards improving the socio-economic condition of low-income households, development organizations offer a repertoire of initiatives. This study focused on the impacts of access to working capital and enterprise development training programs, on the performance and sustainability of micro-enterprises owned and managed by low-income households, in the state of Kelantan, Peninsular Malaysia. The data of 450 micro-entrepreneurs, was randomly selected from the participants’ list of three development organizations servicing Kelantan: Amanah Ikhtiar Malaysia (AIM); National Entrepreneurs Economic Group Fund (TEKUN); and Malaysia Fisheries Development Board (LKIM). This study revealed several participation indicators (i.e., years of participation, total number of trainings, total number of training hours received, and number of center meetings or discussions attended, etc.), which have a positive effect on micro-enterprise performance and sustainability. However, the findings were inconclusive as one of the key participation indicators, ‘total amount of economic loans received’, showed a negative (not statistically significant) effect on micro-enterprise performance and sustainability. This study expanded the limited literature on micro-enterprise performance and sustainability, and the role of working capital and enterprise development training programs; thus providing a clearer understanding of the effectiveness of current development initiatives.